2005
DOI: 10.1007/bf03184093
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of the flowing ground water impacting on coalbed gas content

Abstract: The hydrogeological condition affects the coalbed gas storage dramatically. In an area of stronger hydrodynamics, the coal has a lower gas content, while a higher gas content exists in an area of weaker hydrodynamics. Obviously, the flowing groundwater is harmful to coalbed gas preservation. But few researches focus on the mechanism of how the flowing water diminishes the coalbed gas content. Based on the phenomenon that the flowing groundwater not only makes coalbed gas content lower, but also fractionates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that the meteoric and surface water might flow into the deeper strata of the Shanxi Formation, influenced by the Liulin Nose Structure (Li et al, 2014). Since 13 CH 4 is much more easily transported away by water, the strong hydrodynamic conditions could cause the carbon isotopes of coalbed methane to become lighter (Li et al, 2014;Qin et al, 2005Qin et al, , 2006. Thus, the light carbon isotopes of methane and high N 2 content measured in this study might also be related to past complex tectonic movements that created strong hydrodynamic conditions.…”
Section: Origin Of Hydrocarbon Gasesmentioning
confidence: 99%
“…Previous studies have shown that the meteoric and surface water might flow into the deeper strata of the Shanxi Formation, influenced by the Liulin Nose Structure (Li et al, 2014). Since 13 CH 4 is much more easily transported away by water, the strong hydrodynamic conditions could cause the carbon isotopes of coalbed methane to become lighter (Li et al, 2014;Qin et al, 2005Qin et al, , 2006. Thus, the light carbon isotopes of methane and high N 2 content measured in this study might also be related to past complex tectonic movements that created strong hydrodynamic conditions.…”
Section: Origin Of Hydrocarbon Gasesmentioning
confidence: 99%
“…[8], and therefore, some the researchers always put them together to compare, such as the differences in cause of formation, evolutionary stage and thermal evolution temperature ate different during the natural gas generation [9]; specific to the state of occurrence, the content of adsorbed gas in the coalbed methane is lower; the shale gas has little effect by structural conditions, while the coalbed methane is different. In China's Ordos Basin and Qinshui Basin, you can also see the coalbed methane and shale gas symbiosis [10]. gas exploration and development.…”
Section: Formation Conditions Of the Shale Gasmentioning
confidence: 99%
“…15 coal seam exhibits significant thickness, high adsorption capacity, moderate gas content, low critical desorption pressure, and substantial gas production potential (Jiang et al, 2022). At present, the commercial development of CBM from high-rank coal reservoirs in Qinshui Basin has achieved remarkable results (Nie et al, 2000;Qin et al, 2005;Chen et al, 2015;Wang et al, 2024b).…”
Section: Introductionmentioning
confidence: 99%